Making sense of public opinion : American discourses about immigration and social programs - Strauss, Claudia, 1953- (New York : Cambridge University Press, 2012)
'Americans express contradictory views on immigration and social welfare programs. Claudia Strauss proposes that these views are formed not from standard ideologies or broad values, but from conventional ways of speaking about topics. The wording of a survey question or political message may cue one specific discourse, while a slightly different wording can trigger opposing opinions held by the same speaker. By identifying and describing common vernacular discourses, this book illustrates how discourses construct our opinions on immigration and social welfare. This study draws on interviews with people from various backgrounds to demonstrate how we acquire conventional discourses from our opinion communities. Immigration and Social Programs explains what conventional discourses are, how to study them, and why they are fundamental elements of public opinion and political culture'--
'Including'Mexican American discourses and the theory of divergence' by Hannah Pick.'--T.P.
Includes bibliographical references and index.
Keywords: Immigrants -- United States -- Public opinion; Public welfare -- United States -- Public opinion; Public opinion -- United States; United States -- Emigration and immigration -- Public opinion